Pengaruh Disiplin Kerja Terhadap Kinerja Guru PNS Pada SD Negeri 37 Pekanbaru - Syafrina, Nova (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
The purpose of this study was to determine the effect of work discipline on the performance of civil servant teachers at SD Negeri 37 Pekanbaru. The population in this study were 31 civil servant teachers and the research sample was 31 civil servant teachers. The research method used is descriptive method with a quantitative approach. The average score for the entire statement about Work Discipline is 4.28, meaning that the respondent's answer to the statement about the Work Discipline of PNS Teachers at SD Negeri 37 Pekanbaru is strongly agreed. Meanwhile, the respondents' answers to the performance statement averaged 4.19, which means agree. The data analysis used is simple linear regression with the regression results obtained namely Y = 10,339 + 0.622X, which has a positive relationship direction, that is, if the Work Discipline variable increases, the Performance variable will increase. Based on the results of the t test, it was found that the tcount was 6.264 > ttable 2.04523 with a significant level of 0.000 <0.05. This means that work discipline has a positive and significant effect on the performance of civil servant teachers at SD Negeri 37 Pekanbaru. The R square value of 0.575 or 57.5% means that the Work Discipline variable has an influence on teacher performance of 57.5%.